Adsorption of Sulphur in Biogas by Activated Carbon Derived From Mangrove Fruits (Rhizopora stylosa) as Solid Residue of Natural Dyes Extraction - Paryanto, Paryanto; Wibowo, Wusana Agung; Saputra, Nandika Aji; Setyawati, Rosana Budi (Universitas Diponegoro, 2019)
Hydrogen sulfide (H2S) is considered as impurity in biogas. H2S could react to form sulfur dioxide (SO2) and sulfuric acid (H2SO4) during the burning process. The corrosive property of these compounds possibly cause damage the power plant system. Overcoming this problem, activated carbon impregnated with KOH has been proven to work very well in adsorbing H2S. On the other hand, mangrove fruits pulp residue from the natural dyes extraction process has not utilized. Mangrove (Rhizopora stylosa) fruits contain about 50% fixed carbon which is possibly made as activated carbon. The purposes of this research were to determine the adsorption efficiency of H2S in biogas using activated carbon derived from mangrove fruits residue and to determine isotherm equilibrium constants for adsorption. The small scale adsorption devices consist of cooler, flow stabilizer, flow regulator, flow meter and column adsorber. At certain flow rate, biogas was sampled in every 10 minutes and then analyzed using portable H2S gas analyzer. Â Temperatures of biogas entered the adsorption column were in the range of 33-34oC. The optimum biogas flow rate was 4 liter per minute (lpm) for 250 grams (16 cm of height) of activated carbon. We found the adsorption efficiency was decreased by time and still reached 79.6% for 50 minutes contact time. Based on coefficient of correlation value (R2) on isotherm model, Langmuir model is more suitable for the H2S adsorption of biogas in this study. We found the Langmuir equilibrium constant k was 0.033 and maximum adsorption capacity (x/m)max was 0.284 mg/mg.